Occurrence of gastrointestinal helminths in horses and risk factors for infection. (January 2017) - Balzan, Alexandre; Cazarotto, Chrystian; Grosskopf, Rhayana; Machado, Gustavo; Tonin, Alexandre; Silva, Aleksandro
Abstract This study aimed to monitor the occurrence of gastrointestinal parasites in horses evaluating different rural properties in Santa Catarina State, Southern Brazil. Fresh samples of feces were collected and processed by the McMaster technique, quantifying the number of eggs per gram of feces (EPG), followed by coproculture for identification of helminths. The population investigated was composed of 111 horses of varying ages (1–27 years, 63 males and 48 females). Among all the animals evaluated, 76 animals showed EPG ≥50, representing 63.96 % (IC95 % 54.24–72.70) of samples positive for gastrointestinal helminths. The EPG values ranged from 0 to 5600, with EPG average set as 490. There was a great variation among EPG in different farms. The anthelmintic treatments were carried out in all properties, most of them ranging from 30 to 90 or more 90 days. However, when we correlated the interval of treatment with EPG values, we did not observe significant difference for these variables (P > 0.05). Similarly, there was also no relation between EPG with age and sex of horses (P > 0.05), showing that the EPG values are not dependent of these two independent variables. In coproculture, 40 % of the evaluated properties had only the presence ofStrongylus spp., while 60 % had mixed infection ofStrongylus sp. andTrichostrongylus sp. With our results, we conclude that approximately 64 % of the horses of this study were positive for gastrointestinal parasites.